USE OF GEOPHYSICAL TECHNIQUES FOR ANALYSIS OF TRACE METALS IN A CEMETERY UNSATURATED SOIL ZONE - da SILVA, Francisco Carlos [UNESP]; Cavallaro, Francisco de Assis [UNESP]; Aquino, Wagner França [UNESP]; Almeida, Emerson Rodrigo [UNESP]; Tonello, Paulo Sérgio [UNESP] (UNESP - Universidade Estadual Paulista, 2022)
The purpose of this research was to apply two geophysical methods [Electrical Imaging Technique (RI) and Inductive Electromagnetic Technique (EM-31)] to verify this tool’s efficiency in locating in subsurface contamination plumes and/or metal ions released by decomposition of corpses and their shells at Necrópole Nossa Senhora Aparecida, Piedade, SP. This research was carried out from October 2015 to September 2016. In the first phase, we used the Electrical Imaging technique and later we applied the electromagnetic technique. This period between one investigation and another was useful to verify if anomalies changed during that period. Results showed that localized anomalies did not move and that results of both methodologies were similar, considering limitations of each technique.).
UTILIZAÇÃO DE TÉCNICAS GEOFÍSICAS PARA ANÁLISE DE METAIS TRAÇO EM ZONA DE SOLO NÃO SATURADO DE CEMITÉRIO
Keywords: Cemetery; Electrical Imaging Technique (RI); Geophysics; Inductive Electromagnetic Technique (EM-31); Potentially toxic metals